Samurai II duel at Ichijoji Temple - Takimura, Kazuo; Inagi, Hiroshi; Janus Films ([United States] : Janus Films, 1967)
Summary: After years on the road establishing his reputation as Japan's greatest fencer, Takezo returns to Kyoto. Otsu waits for him, yet he has come not for her but to challenge the leader of the region's finest school of fencing. To prove his valor and skill, he walks deliberately into ambushes set up by the school's followers...
Cast: Toshiro Mifune, Koji Tsuruta, Ko Mihashi, Kokuten Kodo, Michi Yo Kogure
VCD format
Keywords: Samurai films; Man-woman relationships in motion pictures